IMPLEMENTASI PEMBELAJARAN PAI SERTA PENANAMAN TOLERANSI BERAGAMA PADA SD FRANSISKUS PADANG PANJANG - Azwarhadi, Azwarhadi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2016)
This research was aimed at undertanding the implementation of instructional Islamic Education in Primary School Fransiskus Padang Panjang, the non Islamic institution. This research was qualitative by applying interview as instrument. The results obtained indicate that the Primary School Fransiskus Padang Panjang gave good service for Islamic students to learn Islamic Education. Â Keywords: Implementasi, Pendidikan Agama Islam, Toleransi Beragama